2021
DOI: 10.46827/ejes.v8i6.3770
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Impact of Covid-19 on Students at Institutions of Higher Learning

Abstract: <p>Students at higher institutions of learning are more susceptible to psychosocial problems compared to the general public. These may further be exacerbated by the measures put in place to curb the spread of COVID-19. This mixed methods study examined the factors associated with the psychosocial impact of COVID-19 on students’ financial stability, interpersonal relationships and worries related to achieving academic milestones. Data comprised of a series of closed and open-ended questions collected via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Another survey that studied the impact of COVID-19 on students confirmed that the status of being a student was associated with a higher frequency of depressive symptoms, anxiety symptoms, perceived stress and suicidal thoughts ( Akin- Odanye et al, 2021a ). The research literature also elaborated on the impact of COVID-19 on the mental health of students all across the world.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another survey that studied the impact of COVID-19 on students confirmed that the status of being a student was associated with a higher frequency of depressive symptoms, anxiety symptoms, perceived stress and suicidal thoughts ( Akin- Odanye et al, 2021a ). The research literature also elaborated on the impact of COVID-19 on the mental health of students all across the world.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, where students were surveyed to understand the mental health impact of COVID-19 on higher institutions students. results deliberated that financial stability, interpersonal relationships and worries related to achieving academic milestones were the major factors that triggered mental health problems among students ( Akin- Odanye et al, 2021a ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Akin-Odanye et al [62] carried out a mixed-method study to examine the issues related to the mental impacts of the Coronavirus 2019 pandemic on students' fiscal steadiness, interpersonal relations, and worries connected to attaining instructional milestones.…”
Section: Review Of the Literaturementioning
confidence: 99%